Horizontal Dynamic Response of Pile Group Foundation in Liquefied Soil Under Vertical Load - HU Anfeng, CHEN Yiyang, XIAO Zhirong, CHEN Zheng (Shanghai Jiaotong Daxue xuebao, 2024)
The horizontal vibration model of partially buried pile group under vertical load is established based on Biot saturated porous media theory, considering the flow characteristics of liquefied soil. Considering the pile-soil coupling and continuous displacement conditions, the pile interaction factor solutions and the horizontal dynamic pile impedance solutions in liquefied soil under complex conditions are obtained using the variable separation method and the operator decomposition method. Parameter studies are conducted on liquefied soil characteristics and vertical loadings. The results show that at the same vibration frequency, the horizontal dynamic.pngfness of pile group decreases with the increase of surface liquefied soil thickness. When the liquefaction thickness is large, the dynamic.pngfness decreases significantly with the increase of frequency, and a negative.pngfness appears. Vertical pile top loading can reduce the dynamic.pngfness of pile group in liquefaction soils. The weakening effect becomes more obvious with the increase in the thickness of liquefied soil.